Experimental investigation on effect of fin shape on the thermal-hydraulic performance of compact fin-and- tube heat exchangers - P., Moorthy; A. N., Oumer; M., Ishak (IOP Publishing, 2018)

(untitled)
The aim of this paper is to investigate the effect of fin shapes on the performance of compact finned flat tube heat exchangers. Three types of fin shapes namely plain, wavy, and rectangular grooved fins attached to three by three arrays of flat tube banks were considered. Moreover, the tubes were deployed in in-line and staggered arrangements. In addition to the fin shapes, the air velocity and the tube inclination angles were varied and the thermal-hydraulic performance was analysed. On the other hand, the temperatures at the tube surfaces were kept constant to produce constant heat flux throughout the study. The results showed that as flowrate increases, the heat transfer increases, however, the friction factor decreases. Staggered arrangement produces higher heat transfer and friction factor than inline fin. Moreover, the rectangular fin is the best in terms of high heat transfer however the drawback of high friction factor leads the fin to have the least efficiency of all. On the other hand, plain fin had the least heat transfer performance however the highest efficiency was achieved. Therefore, plain fin should be used when efficiency is prioritized and rectangular fin when high heat transfer is desired.